2000
DOI: 10.1037/h0089436
|View full text |Cite
|
Sign up to set email alerts
|

Filial therapy with Native Americans on the Flathead Reservation.

Abstract: This study was designed to determine the effectiveness of the 10week filial therapy model as an intervention for Native American parents and their children residing on the Flathead Reservation in Montana. Native American parents significantly increased their level of empathy in their interactions with their children. Children significantly increased their level of desirable play behaviors with their parents.According to 1990 census figures 1.75 million people in the United States consider themselves to be memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 20 publications
2
26
0
Order By: Relevance
“…The findings in the present study are similar to those of other studies (Bratton, 1993;Chau & Landreth, 1997;Costas & Landreth, 1999;Glover & Landreth, 2000;Harris & Landreth, 1997;Landreth & Lobaugh, 1998;Yuen, 1997).…”
Section: Parental Acceptancesupporting
confidence: 83%
See 2 more Smart Citations
“…The findings in the present study are similar to those of other studies (Bratton, 1993;Chau & Landreth, 1997;Costas & Landreth, 1999;Glover & Landreth, 2000;Harris & Landreth, 1997;Landreth & Lobaugh, 1998;Yuen, 1997).…”
Section: Parental Acceptancesupporting
confidence: 83%
“…Generally, these studies (Chau & Landreth, 1997;Glover & Landreth, 2000;Jang, 2000;Yuen, 1997) show that filial therapy is an effective intervention for culturally …”
Section: Filial Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, multiple research studies involving CPRT have demonstrated that filial therapy leads to increases in parents' acceptance of their children (Bratton & Landreth, 1995;Chau & Landreth, 1997;Costas & Landreth, 1999;Harris & Landreth, 1997;Kale & Landreth, 1999;Landreth & Lobaugh, 1998;Lee & Landreth, 2003;Tew, Landreth, Joiner, & Solt, 2002;Yuen, Landreth, & Baggerly, 2002). In addition, multiple studies have demonstrated that participation in CPRT increases parents' empathic behaviors toward their children (Bratton & Landreth, 1995;Carnes-Holt, 2010;Chau & Landreth, 1997;Costas & Landreth, 1999;Ferrell, 2004;Glover & Landreth, 2000;Harris & Landreth, 1997;Jang, 2000;Kidron, 2004;Lee & Landreth, 2003;Smith & Landreth, 2003;Yuen et al 2002) . Winek et al (2003) found that parents facilitated play sessions by demonstrating behaviors of acceptance and encouragement, and children facilitated play sessions by expressing emotions.…”
Section: Cprt and Experiential Family Therapymentioning
confidence: 99%
“…American parents on the Flathead Reservation (Glover & Landreth, 2000). Villarreal (2008) found changes in internalizing behaviors for English speaking Hispanic parents.…”
Section: Efficacy Of Filial Therapymentioning
confidence: 99%